Acupuncture enhances fatty acid catabolism and immune modulation in children with autism - Xu, Jinbo; Bao, Chao (Frontiers in Psychiatry, 2025)
Autism spectrum disorder (ASD) is a heterogeneous neurodevelopmental condition with limited effective therapies targeting its underlying biological mechanisms. Acupuncture has shown clinical promise in improving core ASD symptoms, yet its molecular effects remain poorly understood. This study aimed to investigate the systemic mechanisms by which acupuncture exerts therapeutic effects in ASD, using an integrated plasma-based proteomic and metabolomic approach. Twenty children were enrolled, including 10 diagnosed with ASD and 10 age- and sex-matched typically developing controls. The ASD group received a 12-week standardized acupuncture intervention. Plasma samples were collected before and after treatment, and analyzed using data-independent acquisition-based LC-MS/MS for proteomics and high-resolution mass spectrometry for metabolomics. Differentially expressed proteins and metabolites were identified across healthy controls, pre-treatment, and post-treatment ASD groups, followed by pathway enrichment and integrated network analysis. Acupuncture significantly modulated biological pathways related to immune regulation, mitochondrial oxidative phosphorylation, glycolysis, folate biosynthesis, lipid metabolism, and fatty acid degradation. Notable differentially expressed proteins included CD59 and CD5L, ATP5F1A and ALDOC, and HYAL1. Metabolomic profiling revealed altered levels of lipids, lipid-like molecules, benzenoids, and folate-related metabolites, implicating changes in neurochemical balance and detoxification capacity. Fatty acid degradation pathways were also enhanced, suggesting a systemic metabolic shift toward an anti-inflammatory state. Integrating proteomic and metabolomic data, the results support a multi-system mechanism through which acupuncture restores immune–metabolic homeostasis, consistent with the holistic therapeutic framework of traditional Chinese medicine. The identification of candidate biomarkers such as CD59, ATP5F1A, and ALDOC offers potential tools for therapeutic monitoring and mechanistic insight. This study presents the first multi-omics evidence for the biological basis of acupuncture in ASD and provides a rationale for individualized interventions. These findings support future research integrating acupuncture with metabolic, nutritional, or immunological therapies. Larger-scale, controlled trials with functional validation of molecular targets are warranted to confirm these findings and guide clinical translation.Clinical Trial Registrationhttps://itmctr.ccebtcm.org.cn/mgt/project/view/896756278374891597/, identifier ITMCTR2025000067.